Domestic violence in the clinical practice of gynecologists and obstetricians - Bauerová, Alena; Nosková, Pavlína (Ceska gynekologie, 2022)
The issue of domestic violence is neglected in current medical practice and the dia-gnosis associated with it thus escapes the attention of medical professionals. In this case report, we demonstrate rare and typical diseases of abused women, which should become warning signs for physicians (red flags) and lead them to screen domestic violence and intervene early. Failure to recognize domestic abuse as the cause of chronic health problems leads to lasting consequences and economically and personally burdens the health care system. Healthcare professionals of all specialties encounter abused women during their clinical practice and can thus actively participate in the prevention of domestic violence. However, it is women of reproductive age who are most at risk, so educating gynecologists and obstetricians on this issue is crucial. The aim of this article with a case study is to demonstrate the syndrome of a battered woman, its recognition and the possibility of immediate and brief intervention.
Keywords: bité ženy; Female; postdural puncture headache; Gynecology; chronic subdural haematoma; domácí násilí; gynekologie; ženské pohlaví; Humans; Physicians; Domestic violence; lidé; Domestic Violence; domestic violence; lékaři; chronic subdural hematoma; Battered Women